2004
DOI: 10.1103/physrevc.70.054306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different baryon impurities

Abstract: We demonstrate the different effect of different baryons impurities on the static properties of nuclei within the framework of the relativistic mean-field model. Systematic calculations show that Λ + c and Λ b has the same attracting role as Λ hyperon does in lighter hypernuclei. Ξ − and Ξ 0 c hyperon has the attracting role only for the protons distribution, and has a repulsive role for the neutrons distribution. On the contrary, Ξ 0 and Ξ + c hyperon attracts surrounding neutrons and reveals a repulsive forc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
16
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
9
16
0
1
Order By: Relevance
“…However the photon field, which is more dominant, compensates for the change in proton radii, so that both the proton and neutron radii decrease at the neutron dripline. This in agreement with the work by Tan et al, 26 where on switching off the coupling of the Ξ − to the ρ-meson, only the proton radius decreased, leaving the neutron radius unchanged. As the shrinkage due to the Ξ − can be seen even at very low mass, it will be interesting to look for such changes experimentally.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However the photon field, which is more dominant, compensates for the change in proton radii, so that both the proton and neutron radii decrease at the neutron dripline. This in agreement with the work by Tan et al, 26 where on switching off the coupling of the Ξ − to the ρ-meson, only the proton radius decreased, leaving the neutron radius unchanged. As the shrinkage due to the Ξ − can be seen even at very low mass, it will be interesting to look for such changes experimentally.…”
Section: Resultssupporting
confidence: 93%
“…3, it can be seen that at the p-dripline of Ξ − hypernuclei the rms charge radius decreases while the neutron radius increases. A similar effect was seen by Tan et al 26 for nuclei away from dripline. There, a slow decrease in this effect with mass was seen.…”
Section: Resultssupporting
confidence: 85%
“…The quest for proton or neutron magic numbers in the elusive mass region of superheavy nuclei is of utmost importance as the mere existence of superheavy nuclei is the result of the interplay between the attractive nuclear force (shell effects) and the large disruptive coulomb repulsion between the protons that favours the fission [39,40]. It is well established that 2,8,20,28,50,82 and 126 are the nucleonic magic number. In addition to this, Z = 120 and N = 172, 184 are predicted to be next magic number by various theoretical models in superheavy mass region [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…A study analysing the default mode of cats found that the anticorrelations between the DMN and the DAN were found only 20% of the time suggesting a role of DMN in attention [24]. People with disorders like ADHD, Parkinson's disease, Alzheimer's have shown to have differential connectivity in the DMN which can be altered using drugs [25]. The recent use of continuous attention tasks demonstrated a complex dynamics between DAN-DMN activity with task load and attentional control [26].…”
Section: Introductionmentioning
confidence: 99%